2022
DOI: 10.3389/fpls.2022.910228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Plant Trichome Development

Abstract: Plant trichomes, protrusions formed from specialized aboveground epidermal cells, provide protection against various biotic and abiotic stresses. Trichomes can be unicellular, bicellular or multicellular, with multiple branches or no branches at all. Unicellular trichomes are generally not secretory, whereas multicellular trichomes include both secretory and non-secretory hairs. The secretory trichomes release secondary metabolites such as artemisinin, which is valuable as an antimalarial agent. Cotton trichom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 313 publications
(424 reference statements)
0
25
0
Order By: Relevance
“…Chinese cabbage can be divided into trichomes and without trichomes types. Although Chinese cabbage trichomes play an obvious role in increasing leaf thickness to reduce heat of epidermis, loss of water, and defense against insect pathogen invasion and mechanical injury [ 14 , 15 ], it also affects the consumption quality, and sometimes even cause stabbing injury to human body. Therefore, how to remove trichomes or regulate the formation of trichomes is extremely important for fruit and vegetables breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese cabbage can be divided into trichomes and without trichomes types. Although Chinese cabbage trichomes play an obvious role in increasing leaf thickness to reduce heat of epidermis, loss of water, and defense against insect pathogen invasion and mechanical injury [ 14 , 15 ], it also affects the consumption quality, and sometimes even cause stabbing injury to human body. Therefore, how to remove trichomes or regulate the formation of trichomes is extremely important for fruit and vegetables breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that transcription factors are involved in the differentiation of plant epidermal structure and often play a key regulatory role upstream of the epidermal structure development signaling pathway. For example, in the development of trichome and root hairs of model plants such as A. thaliana , tomato, and Artemisia annua , MYB-type transcription factors such as GL1, TTG1, CPC, and AaMIXTA1 play a key role in the fate-determining stage of trichome and root hair development ( Han et al., 2022 ). Unlike A. thaliana and other non-halophyte, the leaves of L. bicolor have no trichome structure, but the time node of the initial development of L. bicolor salt glands is almost the same as that of A. thaliana trichome, which is earlier than the stomata.…”
Section: Discussionmentioning
confidence: 99%
“…In 1990, Wiehe and Breckle proposed the development mechanism model of a multicellular salt gland of L. bicolor . It was assumed that the salt gland is a sixteen-cell complex formed by five successive divisions of a protoepidermal cell ( Han et al., 2022 ). This complex comprises four secretory cells, four adjacent cells, four inner cup cells, and four outer cup cells ( Wiehe and Breckle, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trichomes are highly specialized epidermal protrusions, often located in the leaves, stems, flowers, petioles, sepals, tendrils, seed coats, and other parts, and play an important role in defending against alien organisms such as insects or large herbivores (biological stress) and coping with abiotic stress (Liu et al., 2016; Zhu et al., 2018). Trichomes originate from protocortical cells and have different manifestations in different plants (Han et al., 2022). Prickles and trichomes have certain correlations and similarities (Swarnkar et al., 2021; Zhou, Simonneau et al., 2021), and some studies suggest that spines originate from multiple cell divisions in the epidermis, develop from modified glandular trichome, and then lignify to form rigid spiny appendages, which are the result of the lignification of epidermal hairs (KelloggAllicia et al., 2011; Khadgi & Weber, 2020; Qian et al., 2021).…”
Section: Introductionmentioning
confidence: 99%